2010
DOI: 10.1162/jeea_a_00008
|View full text |Cite
|
Sign up to set email alerts
|

How Important Is Selection? Experimental vs. Non-Experimental Measures of the Income Gains from Migration

Abstract: Measuring the gain in income from migration is complicated by non-random selection of migrants from the general population, making it hard to obtain an appropriate comparison group of non-migrants. This paper uses a migrant lottery to overcome this problem, providing an experimental measure of the income gains from migration. New Zealand allows a quota of Tongans to immigrate each year with a lottery used to choose amongst the excess number of applicants. A unique survey conducted by the authors in these two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
188
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(190 citation statements)
references
References 7 publications
2
188
0
Order By: Relevance
“…The results show monetary gains to the immigrants similar to the first year effects found by McKenzie et al (2010) and a little less than the impacts after four years reported by Stillman et al (2015). The economic payoff to migrating to a richer country seems to come immediately, and then not grow further, notwithstanding various investments by the immigrants in qualifications, internal mobility, and occupational change.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…The results show monetary gains to the immigrants similar to the first year effects found by McKenzie et al (2010) and a little less than the impacts after four years reported by Stillman et al (2015). The economic payoff to migrating to a richer country seems to come immediately, and then not grow further, notwithstanding various investments by the immigrants in qualifications, internal mobility, and occupational change.…”
supporting
confidence: 51%
“…About 1500 Tongans come to New Zealand each year under this scheme (Gibson and McKenzie, 2014a); more than six times the number coming via PAC settlement migration. There is no formal interaction between these two migration pathways (seasonal workers are told they have no option to settle), and they select from different parts of the skills distribution in Tonga with the PAC applicant pool positively selected (McKenzie et al, 2010) and the seasonal workers negatively selected by a focus on people not in formal employment (Gibson and McKenzie, 2014b). Moreover, the seasonal workers go to regional New Zealand while Auckland is the first destination for most PAC migrants.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If those in the home country are worse off than the migrant, altruism induces migrants to make donations for their home country. Altruism may play an important role as migrants typically multiply their income by working abroad (Clemens et al, 2008;McKenzie et al, 2010) thus widening the income gap between migrants and those who stay behind. The altruism motive predicts that donations increase with migrants' income and the degree they are still attached to their home country.…”
Section: Introductionmentioning
confidence: 99%